A redescription of the endemic Madagascan genus Tricompastes (Hemiptera: Heteroptera: Pentatomidae) - Kment, Petr; Baena, Manuel (Zootaxa, 2015)
The endemic Madagascan genus Tricompastes Cachan, 1952 (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Triplatygini), containing a single species—Tricompastes gigas Cachan, 1952, is redescribed and illustrated, including first descriptions of male and female genitalia. First exact localities of the species are provided. Lectotype of T. gigas is designated.